Modelagem numérica do escoamento em válvulas de compressores alternativos pelo método da fronteira imersa com refinamento adaptativo - Barbi, Franco [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
In refrigeration compressors, the suction and discharge valves are responsible for the retention and passage of the refrigerant fluid from the suction chamber to the cylinder, and from the cylinder to the discharge chamber. Valve system designers seek for valves with small overall flow pressure drop in order to increase the compressor efficiency. As the opening and closing of the valves are caused by the forces produced by the refrigerant flow, the understanding of the flow through the valve is of fundamental importance in order to enhance the efficiency of the valve system. The numerical simulation of the flow is an efficient method to perform this task. Due to the complex geometry usually found in this type of valve, simplified geometries have been used to represent the valve, particularly the radial diffuser geometry. The Immersed Boundary method is very attractive when it comes to complex geometries and fluid-structure interaction, for it allows the simulation of fluid flow past complex geometries, with boundary movement, without complicating the mesh generation process. In the present work, the Multi-Direct Forcing introduced by Wang (2007) is used for the rigid body force calculations. The incompressible, viscous flow is solved by the AMR3D (Adaptive Mesh Refinement 3D) which contains a semi-implicit time discretization scheme of second order and a projection method for the pressure-velocity coupling. The mesh generated by the code consists in sequences of nested, progressive finer rectangular grid patches, which dynamically adapts to the flows vorticity field and the presence of an immersed boundary. The numerical method is validated with experimental data obtained for the flow through the radial diffuser's geometry. A model that represents well the real geometry of the real valve is proposed, with angular movement imposed for valve opening and closing simulation. Results show that the ...

Em compressores de refrigeração, as válvulas de sucção e descarga são responsáveis pela retenção e passagem do fluido refrigerante da câmara de sucção ao cilindro, e do cilindro à câmara de descarga. Projetistas trabalham para que essas válvulas tenham baixa perda de carga, aumentando a eficiência do processo. Como a abertura e o fechamento das válvulas são realizados por forças do próprio escoamento, o entendimento do escoamento através das mesmas é fundamental para melhorar o desempenho do sistema de válvulas. Esta tarefa pode ser realizada eficientemente com o uso de ferramentas numéricas. Devido à complexidade da geometria real das válvulas, encontram-se na literatura diversos trabalhos que utilizam modelos simplificados na representação das válvulas. Em particular, a geometria do difusor radial se destaca como o modelo simplificado mais utilizado nesse tipo de escoamento, e importantes conclusões foram obtidas devido ao uso adequado do modelo. O Método da Fronteira Imersa é um método promissor no estudo de problemas de geometria complexa e envolvendo interações de fluido-estrutura. Com esse método, é possível investigar o escoamento em modelos mais complexos, sem grandes complicações no processo de geração de malha. No presente trabalho, utiliza-se o método de Multi-Forçagem Direta proposto por Wang (2007) para os cálculos de forças na representação do corpo rígido. A solução do escoamento incompressível e viscoso é feita através do código AMR3D (Adaptive Mesh Refinement 3D), composto por um esquema de avanço temporal semi-implícito de segunda ordem e um método de projeção no acoplamento pressão-velocidade. A malha gerada pelo código consiste em blocos de refinamento localizado alocados de acordo com uma sequência de níveis de refinamento, que se adapta ao campo de vorticidade e a presença de uma fronteira imersa. O método numérico é...
Keywords: Compressores - Valvulas; Escoamento; Geometria; Compressors Valves